Zoned Audio Distribution: Systematic Review and Optimization Framework in Mosque - Rosad, Safiq; Yudhana, Anton; Sutikno, Tole (ELKHA : Jurnal Teknik Elektro, 2025)
The acoustics of mosques present significant challenges due to their substantial spatial dimensions, highly reflective surfaces, and intricate architectural designs. These characteristics frequently compromise the clarity of sound, which is imperative for religious activities such as sermons and prayers. Despite global advancements in audio technology, centralized sound systems remain the most common choice in many mosques worldwide. However, this approach frequently results in issues such as uneven sound distribution, acoustic dead zones, and excessive reverberation. These factors significantly impact speech intelligibility and overall listener comfort. To address this critical issue, this study presents a systematic literature review spanning from 2003 to 2025. This research also incorporates an initial empirical survey conducted on 77 mosques in Indonesia to provide real-world validation. The survey results empirically corroborated the theoretical problems, revealing that 65% of respondents considered the sound unclear, and less than 50% expressed satisfaction with the current audio system. In light of these findings, the present paper puts forth an integrated optimization framework centered on speaker zoning. The framework synthesizes insights from acoustic engineering, psychoacoustics, and predictive modeling to create a holistic, data-driven solution. The model outlined herein provides a procedural framework for future research endeavors, emphasizing the utilization of professional acoustic simulation tools to achieve uniform sound distribution and high speech intelligibility. This methodological approach guarantees that the acoustic solutions are not only scientifically valid but also user-centric and relevant to the congregation's needs.